1968
DOI: 10.1121/1.1910856
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Auditory Signal in Restricted Sets of Reproducible Noise

Abstract: The detectability of auditory signals in reproducible random noise was studied under two conditions: a single noise used throughout a block of 288 trials, and 12 noises occurring at random, but with equal frequency, throughout a block of trials. Both two-interval forced-choice judgments and judgments of the presence or absence of the signal in single-noise samples were obtained in separate blocks of trials. On individual trials of the forced-choice judgments, the same noise appeared in both intervals. Signal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1969
1969
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Both included Repeat visual sequences, and were made to recur intermittently and randomly. We describe these sequences as ''frozen,'' after that term's use in auditory psychophysics to refer to reproducible noise stimuli (Guttman & Julesz, 1963;Pfafflin, 1968;Pfafflin & Matthews, 1966).…”
Section: Methodsmentioning
confidence: 99%
“…Both included Repeat visual sequences, and were made to recur intermittently and randomly. We describe these sequences as ''frozen,'' after that term's use in auditory psychophysics to refer to reproducible noise stimuli (Guttman & Julesz, 1963;Pfafflin, 1968;Pfafflin & Matthews, 1966).…”
Section: Methodsmentioning
confidence: 99%
“…Buus (1990) measured sound-level discrimination for noise bursts and found that difference limens were smaller when the same noise token was used on all trials. Finally, and although noise was not a target, it was found that presenting the same noise token as a masker for all trials in a pure-tone detection task led to lower signal thresholds, compared to when noise was generated afresh for each trial (Pfafflin, 1968). This was interpreted as a form of memory for the noise token used as a masker.…”
Section: Learning Of Noise Tokensmentioning
confidence: 95%
“…Green, 1964;Pfafflin and Mathews, 1966;Pfafflin, 1968;Bell and Nixon, 1971;Ahumada and Lovell, 1971), but noise intensity, duration, and bandwidth were not varied parametrically in any of these experiments. The present research is an extension of a preliminary study by Raab and Leshowitz (1968).…”
Section: If--as It Appears--discrepancy Between Real and Ideal Listenersmentioning
confidence: 96%